NILAI SOSIAL DALAM NOVEL 172 DAYS KARYA NADZIRA SHAFA - Junita; Haerun Ana; Marwati (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to describe the social values contained in the novel 172 Days by Nadzira Shafa. The expected benefits in this research are: 1) Enriching knowledge, especially in the study of literary works related to social values. 2) This research is expected to provide input to students, especially students of the Indonesian Language and Literature Education Department in reviewing and analyzing novels. 3) By understanding social values, it will add references to research on Indonesian literary works and help readers understand the meaning contained in literary works. This type of research is library research. The method used in this research is descriptive qualitative method. The data used in this research is written data in the form of novel text related to all elements related to social values contained in the novel 172 Days by Nadzira Shafa. The data source in this research is the novel 172 Days by Nadzira Shafa published by Motivaksi Inspir, Banjar, West Java, in 2022 with a page thickness of 241 pages. The technique in collecting data is intensive reading technique by recording, identifying exposure and textual literary works in the form of 172 Days novel book by Nadzira Shafa. The data were analyzed using the sociology of literature approach. Based on the results of data analysis, it is concluded that the results of this study show the form of social values including: (1) religious social values. (2) social value of helping each other. (3) social value of forgiving each other. (4) social value of compassion. (5) social value of responsibility.